JANGER BANYUWANGI: KREASI DAN INOVASI TRADISI LISAN KE PERTUNJUKAN - Anoegrajekti, Novi; Macaryus, Sudartomo; Caturwati, Endang; Iskandar, Ifan; Attas, Siti Gomo (Balai Bahasa Provinsi Jawa Timur, 2022)
Abstract: Janger Banyuwangi has been established since 1918 and designed to present an entertainment for the community. It was firstly called as Damarwulan due to a character -based Damarwulan and celebrated in every eclipse. This study purposed to analyze the creation, character innovation, and performing arts technique. This study was ethnographic study started by inventing literature studies in the form of article, research report, theses, and dissertation. The literature studies were completed by filed data obtained from observation and participation by directly seeing the performance of Janger. The data were analyzed semiotically by positioning every section such as character innovation, performing technique, property, and community's response as evidences that indicated cultural dynamics. This study resulted that character innovation and creativity, performing technique, and interest of audience had become variabkes that determined the popularity of Janger group.